Implementasi Revitalisasi Kawasan Kumuh di Kelurahan Ciptomulyo Malang Berbasis Prinsip Sustainable Development Goals (SDGs): Implementation of Slum Area Revitalization in Kelurahan Ciptomulyo, Malang Based on Sustainable Development Goals (SDGs) Principles - Masitha, Lintang (LPPM Universitas Jambi, 2024)
This study focuses on the implementation of slum area revitalization in Kelurahan Ciptomulyo, Malang, based on Sustainable Development Goals (SDGs) principles. The research aims to evaluate the impact of infrastructure improvement, economic enhancement, and social interventions in creating a healthier, safer, and more sustainable environment. Using a qualitative approach with literature analysis, the study collects secondary data to identify the implementation and effects of the revitalization program. Findings highlight that while physical and social aspects have seen significant improvements, economic revitalization requires more attention to reduce dependency on social aid and ensure sustainable community development. The revitalization aligns with several SDGs, particularly those related to good health and well-being, quality education, clean water and sanitation, sustainable cities and communities, and partnerships for the goals. The study suggests that comprehensive strategies involving economic empowerment and stakeholder collaboration are crucial for achieving sustainable urban revitalization.